The effects of music relaxation and muscle relaxation techniques on sleep quality and emotional measures among individuals with posttraumatic stress disorder - Iris Haimov; Ilana Kremer; Monica Blanaru; Boaz Bloch; Limor Vadas; Naomi Ziv; Zahi Arnon (Mental Illness)
Posttraumatic stress disorder (PTSD), an anxiety disorder with lifetime prevalence of 7.8%, is characterized by symptoms that develop following exposure to traumatic life events and that cause an immediate experience of intense fear, helplessness or horror. PTSD is marked by recurrent nightmares typified by the recall of intrusive experiences and by extended disturbance throughout sleep. Individuals with PTSD respond poorly to drug treatments for insomnia. The disadvantages of drug treatment for insomnia underline the importance of non-pharmacological alternatives. Thus, the present study had three aims: first, to compare the efficiency of two relaxation techniques (muscular relaxation and progressive music relaxation) in alleviating insomnia among individuals with PTSD using both objective and subjective measures of sleep quality; second, to examine whether these two techniques have different effects on psychological indicators of PTSD, such as depression and anxiety; and finally, to examine how initial PTSD symptom severity and baseline emotional measures are related to the efficiency of these two relaxation methods. Thirteen PTSD patients with no other major psychiatric or neurological disorders participated in the study. The study comprised one seven-day running-in, no-treatment period, followed by two seven-day experimental periods. The treatments constituted either music relaxation or muscle relaxation techniques at desired bedtime. These treatments were randomly assigned. During each of these three experimental periods, subjects’ sleep was continuously monitored with a wrist actigraph (Ambulatory Monitoring, Inc.), and subjects were asked to fill out several questionnaires concerned with a wide spectrum of issues, such as sleep, depression, and anxiety. Analyses revealed a significant increase in objective and subjective sleep efficiency and a significant reduction in depression level following music relaxation. Moreover, following music relaxation, a highly significant negative correlation was found between improvement in objective sleep efficiency and reduction in depression scale. The study‘s findings provide evidence that music relaxation at bedtime can be used as treatment for insomnia among individuals with PTSD.